Mineral Additives in Concrete Durability: A Comprehensive Review - Regmi, Khem Raj; Sahani, Kameshwar; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2023)
The body of literature on concrete using mineral admixtures covers a number of review studies on the durability characteristics of various materials used in concrete, such as fly ash (FA), rice husk ash (RHA), ground granular blast furnace slag (GGBS), fly ash (SF), and met kaolin (MK) are reviewed in this work. The features that are related to durability have been evaluated, and they include permeability, resistance to chloride ion penetrations, abrasion, fire resistance efflorescence. Incorporating mineral admixtures in concrete affects various properties. Concrete's permeability decreases and its ability to resist chloride ion penetration rises when admixtures containing a greater alumina content are used. Use of mineral admixtures enhances compressive strength and enhancing abrasion resistance. Moreover, highly reactive mineral admixtures mitigate efflorescence. Notably, while heating PFA concrete improves fire resistance, it reduces overall durability. SF concrete, on the other hand, behaves similarly to standard concrete but can be more brittle. MK concrete exhibits increased strength at 200°C, but its durability and strength decline at higher temperatures compared to other concrete types.RHA pozzolans can replace OPC up to 15% by weight after curing for up to 200 days without lowering the concrete's compressive strength.